2005
DOI: 10.1097/01.rli.0000185640.48786.f6
|View full text |Cite
|
Sign up to set email alerts
|

Technical Report and Preliminary Clinical Data of a Novel Catheter for Luminal Re-Entry After Subintimal Dissection

Abstract: Although the Outback catheter is safe, the percentage of intraluminal reaccess should be ameliorated through engineering improvements because there is some evidence to suggest that subintimal recanalization could produce improved long-term results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 22 publications
0
25
0
1
Order By: Relevance
“…1,3,4 Hausegger et al 3 used the first-generation model of the Outback system in 10 patients with intermittent claudication as a bailout procedure to cross iliofemoral lesions; they reported a success rate of 80%. Using the same model, Wiesinger et al 4 reported a success rate of only 50%. The low success rate was attributed to insufficient stiffness and sharpness of the system for penetrating, crossing, and puncturing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1,3,4 Hausegger et al 3 used the first-generation model of the Outback system in 10 patients with intermittent claudication as a bailout procedure to cross iliofemoral lesions; they reported a success rate of 80%. Using the same model, Wiesinger et al 4 reported a success rate of only 50%. The low success rate was attributed to insufficient stiffness and sharpness of the system for penetrating, crossing, and puncturing.…”
Section: Discussionmentioning
confidence: 99%
“…However, heavily calcified lesions limited the re-entry success rate to as low as 50% in early reports using the first-generation Outback catheter. 4 Therefore, the system was redesigned to deploy the needle via a lateral port from the integral hypotube that previously ended in a curved retractable needle. 1,3,4 Using the redesigned system, we were able to achieve a 95% revascularization rate with the Outback LTD catheter in 20 cases of chronic SFA occlusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown variable success rates of 50 to 100% for re-entry devices in the treatment of infra-inguinal arterial occlusive diseases (2,7,8).…”
Section: Introductionmentioning
confidence: 99%